Maternal oxygen inhalation affects the fetal hemodynamic in low-risk with uncomplicated late pregnancy - Xiu-Qin Wu; Xiao-Feng Yang; Lin Ye; Xiao-bin Zhang; Yong-Qiang Hong; Wei-Hsiu Chiu (European Journal of Medical Research)
Abstract Background Maternal oxygen inhalation during labor has not been shown to provide significant benefits to newborns. However, its impact on fetal hemodynamics in late pregnancy remains uncertain. Objective This study aimed to investigate the association between maternal oxygen inhalation in the late trimester and changes in fetal hemodynamics. Specifically, we assessed the short-term effects of maternal oxygen administration on fetal Doppler parameters and evaluated whether this practice has potential benefits or risks for the fetus. Study design These retrospective data were obtained from singleton pregnancies who underwent a after 32+0 weeks prenatal ultrasound examination between January 2022 and December 2022. Participants were categorized into oxygen inhalation and non-oxygen inhalation groups. Oxygen inhalation was administered based on maternal request, primarily due to concerns about hypoxia from prolonged mask use during the COVID-19 pandemic, rather than clinical indication. Our study analysis was performed in August 2023. In oxygen inhalation group, pregnant women received oxygen inhalation with 3 L/min for 30 min by nasal cannula, and before went to department of ultrasound for sonographic assessment within 1 h. The CPR and PPI were predefined as primary outcomes prior to analysis. Each woman was recorded Doppler index and calculated placental pulsatility index (PPI) and cerebroplacental ratio (CPR). Moreover, fetal cardiac function was assessed within pulsed Doppler or M-mode. Main outcome The primary outcome presented higher PPI, lower CPR, and lower birth weight for the exposure maternal oxygen inhalation group, compare to non-oxygen inhalation group. Results A total of 104 singleton pregnancies were included in the final analysis (oxygen inhalation group: n = 48). No significant differences were observed in the resistance indices of the uterine arteries, umbilical arteries, middle cerebral arteries, descending aorta, ductus venosus, or umbilical vein. However, variations were noted in the oxygen inhalation group. Notably, indices with higher sensitivity for predicting adverse outcomes demonstrated significant differences between groups: PPI was higher in the oxygen inhalation group compared to the non-oxygen inhalation group (0.81 ± 0.12 vs. 0.76 ± 0.11, p < .05), while CPR was also lower in the oxygen inhalation group (1.98 ± 0.56 vs. 2.28 ± 0.70, p < .05). Additionally, birth weight was significantly lower in the oxygen inhalation group compared to the non-oxygen inhalation group (2983.78 ± 468.18 g vs. 3178.41 ± 477.59 g, p < .05). Conclusion Our study found that brief maternal oxygen inhalation in the third trimester was associated with significant changes in fetal hemodynamics, specifically higher PPI and lower CPR. Both of these indices are sensitive markers of unfavorable prenatal outcomes, indicating that maternal oxygen inhalation may adversely affect fetal health. These findings underscore the importance of carefully evaluating the use of oxygen inhalation in pregnant women, especially those in high-risk pregnancies. Additionally, monitoring Doppler indices before and after oxygen administration may help assess fetal well-being and guide clinical decision-making in these situations.